What is a melody? On the relationship between pitch and brightness of timbre - Cousineau, Marion; Carcagno, Samuele; Demany, Laurent; Pressnitzer, Daniel (Frontiers in Systems Neuroscience, 2014)
Previous studies showed that the perceptual processing of sound sequences is more efficient when the sounds vary in pitch than when they vary in loudness. We show here that sequences of sounds varying in brightness of timbre are processed with the same efficiency as pitch sequences. The sounds used consisted of two simultaneous pure tones one octave apart, and the listeners' task was to make same/different judgments on pairs of sequences varying in length (one, two, or four sounds). In one condition, brightness of timbre was varied within the sequences by changing the relative level of the two pure tones. In other conditions, pitch was varied by changing fundamental frequency, or loudness was varied by changing the overall level. In all conditions, only two possible sounds could be used in a given sequence, and these two sounds were equally discriminable. When sequence length increased from one to four, discrimination performance decreased substantially for loudness sequences, but to a smaller extent for brightness sequences and pitch sequences. In the latter two conditions, sequence length had a similar effect on performance. These results suggest that the processes dedicated to pitch and brightness analysis, when probed with a sequence-discrimination task, share unexpected similarities.